A classe hospitalar no contexto da educação de jovens e adultos: intervenções pedagógicas no ABC Nefro - FONSÊCA, Margareth Santos (2018)
This research on the Hospital Class “ABC Nefro” had the general objective to develop pedagogical intervention strategies for students in hemodialysis treatment, aiming at the construction of a digital platform of teaching management. The specific goals were: evaluating the reading and writing abilities of the students; identifying the views of the teachers about the work and creating, in collaboration with these teachers, strategies of educational intervention based on the curriculum of the Youth and Adult Education adopted by “SEMED”, the public entity responsible for the education in the state. The problem of the investigation was the following: Which are the needs for adaptation in the school curriculum to make possible interventions in the education of students in the hospital classroom? Seeking paths to answer this question we built our theoretical and methodological base on the legal grounds of the subjective human rights and on the educational legislations that deal on the topic of this study. We used the approach of the dialectical methodology of Paulo Freire and studies about the curriculum in the critical and post-critical perspective. From an empirical point of view this was an active research with document study, participant observation and applied intervention. It was founded on the methodology of a quantitative and qualitative approach and in content analysis in a group of 14 students going through hemodialysis treatment, between 15 and 72 years old, enrolled on the public system of education in the city of Sao Luis, as well as 5 teachers. The instruments for generation of data used were: a socialdemographic questionnaire; an adapted school performance test; the reading of words from the hospital context; reports, educational planning and semi-structured interview. We built a descriptive analysis based on the data using the Statistical Package for the Social Sciences, in its Portuguese version number 22.0. Among the results on the variables we highlight: age group standard deviation of 50 years old; prevalence of women (70%); low income socioeconomic status (100%); memory difficulties (92,8%); low performance on reading and writing (50%). The study indicated the need for a curriculum adaptation that includes the use of a pedagogical resource better suited to the evidences mentioned and to the learning context of the students. We reached the conclusion that digital mobile technology, in the educational context studied, constitute pedagogical resources that enhance the learning process as well as the learning management.